2019
DOI: 10.1101/715474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recognition of histone H3 methylation states by the PHD1 domain of histone demethylase KDM5A

Abstract: PHD reader domains are chromatin binding modules often responsible for the recruitment of large protein complexes that contain histone modifying enzymes, chromatin remodelers and DNA repair machinery. PHD domains recognize N-terminal residues of histone H3 and are sensitive to the methylation state of Lys4 in histone H3 (H3K4). Histone demethylase KDM5A, an epigenetic eraser enzyme that contains three PHD domains, is often overexpressed in various cancers and its demethylation activity is allosterically enhanc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 69 publications
(93 reference statements)
2
7
0
Order By: Relevance
“…This finding is consistent with the observation of hydrogen bonding between the hydroxyl group of H3T3 and the amide of H3T6, which contributes to the H3 peptide's adoption of a stabilized helical conformation when bound to PHD1, and hydrophobic interactions between the methyl group of H3T3 and the L309 and V330 residues of PHD1. 42 The FP results for the T3 single mutant ligands largely agree with the PI-SAMDI array data, which showed relatively low affinity for each of these ligands except T3Y, which displayed a higher fold enhancement (Figure 4B). Additionally, we observed that PHD1 displays an affinity similar to the wild-type ligand for every Q5 single mutant ligand tested in the FP assay, suggesting that Q5 is dispensable for binding (Table 1, entries 8−14; Figure S4).…”
Section: ■ Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding is consistent with the observation of hydrogen bonding between the hydroxyl group of H3T3 and the amide of H3T6, which contributes to the H3 peptide's adoption of a stabilized helical conformation when bound to PHD1, and hydrophobic interactions between the methyl group of H3T3 and the L309 and V330 residues of PHD1. 42 The FP results for the T3 single mutant ligands largely agree with the PI-SAMDI array data, which showed relatively low affinity for each of these ligands except T3Y, which displayed a higher fold enhancement (Figure 4B). Additionally, we observed that PHD1 displays an affinity similar to the wild-type ligand for every Q5 single mutant ligand tested in the FP assay, suggesting that Q5 is dispensable for binding (Table 1, entries 8−14; Figure S4).…”
Section: ■ Results and Discussionsupporting
confidence: 79%
“…This may be due to charge−charge interactions between the positively charged Q5R residue and the negatively charged E305 and D306 residues in PHD1. 42 We did observe several inconsistencies between the PI-SAMDI and FP results and therefore sought to better understand the sources of this discrepancy. We selected three ligands with which to compare the two assay formats: wild-type, a well-characterized, high-affinity ligand that showed only moderate fold enhancement in the PI-SAMDI array; Q5E, which displayed low fold enhancement in the PI-SAMDI array but showed high affinity in the FP assay; and Q5Y, which showed high affinity in both assays.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In particular, residues D292/Y294/L308 in JARID1A and W1502/W512 in JARID1B, which are required for histone peptide binding, 54. , 55. are affected by neutral missense variants ( Figure 4 (C)–(D)).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, residues responsible for histone peptide binding in PHD3 of JARID1A ( Figure 4 (C)) 53. , 55. and PHD1 of JARID1B ( Figure 4 (D)) 52.…”
Section: Resultsmentioning
confidence: 99%
“…[ 51 ] Interestingly, these PHD domains are also involved in KDM5A DNA damage functions where the PHD1 domain is required to localize KDM5A to DSBs, while the PHD3 domain, which is dispensable for break recruitment, is necessary for KDM5A DSB repair functions downstream of break recruitment (Figure 1A). [ 34,52 ] KDM5A can promote DNA repair and transcriptional silencing through the recruitment of additional effector complexes, including ZMYND8 and the NuRD complex. [ 34 ] At DSBs, ZMYND8 requires the histone acetyltransferase (HAT) TIP60 and its bromodomain (BRD) to localize to breaks, suggesting an important, yet poorly understood, requirement for acetylation in this pathway.…”
Section: Kdm5a As a Par Effectormentioning
confidence: 99%